Health-related quality of life and its determinants among patients with multiple chronic diseases in urban and rural regions of Yichang city - Zi-jing PAN; Yue WU; Liang ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the health-related quality of life (HRQOL) and its determinants among residents with multiple chronic diseases in urban and rural regions of Yichang city, Hubei province, and to provide clues for developing targeted policies for chronic disease management in the population.MethodsUsing stratified multistage random sampling, we recruited 6 757 residents aged ≥ 15 years in urban and rural communities in Yichang municipality and conducted a household questionnaire survey during July - August 2018. Then, we identified a total of 654 participants with two or more clinically diagnosed chronic diseases and assessed their HRQOL with Three-Level EuroQol Five Dimensional Questionnaire (EQ-5D-3L). Tobit regression analysis was adopted in analyses on determinants of the multimorbidity in the patients.ResultsOf the patients with multiple chronic diseases, 366 (56.0%) and 288 (44.0%) lived in urban and rural region. The health utility value for all the patients was 0.947 ± 0.100 and the urban patients had a significantly higher health utility value than the rural patients (0.950 ± 0.110 vs. 0.943 ± 0.085, Z = 11.769; P < 0.001). The results of Tobit regression analysis indicated that the urban patients with following characteristics were more likely to have a higher health utility value: married (β = 0.057), with the education of junior high school (β = 0.091), having physical exercise of 1 - 3 times/week (β = 0.092) and 4 times or more /week (β = 0.190); while, for the rural patients, those having physical exercise were more likely to have a higher health utility value (1 - 3 times/week: β = 0. 0.057, 4 times or more /week: β = 0.051), but those being retired (β = - 0.036) and unemployed /jobless (β = - 0.107) were more likely to have a lower health utility value.ConclusionIn Yichang municipality, the urban community patients with multiple chronic diseases have a relatively higher HQROL and the HQROL is higher among the community patients with frequent physical excercise in urban and rural regions.